Rapid detection of extra‐intestinal pathogenicEscherichia colimulti‐locus sequence type 127 using a specific PCR assay. Issue 2 (February 2019) - O'Hara, Robert William; Jenks, Peter J.; Emery, Matthew; Upton, Mathew
Abstract : Purpose. : Members of the ST127 uropathogenic E. coli (UPEC) clone have a high virulence potential and are also highly virulent in insect infection models. However, strains of this lineage are reported in relatively low numbers in many studies. ST127 strains are also usually widely susceptible to antibiotics and, consequently, their true prevalence may be under‐recognized as they will be eradicated during empirical therapy. A genuine concern is the possibility that members of this highly virulent lineage will acquire resistance, leading to a more serious threat. The aim of this study was to design and validate a PCR assay specific to ST127. Methodology. : Genomic sequences obtained from various UPEC isolates from the leading clones were used in comparative genomic analyses to allow identification of highly discriminatory sequences specific to E. coli ST127. The fliC (flagellin) and a homologue of the upaG (autotransporter adhesin) gene were identified as meeting our criteria and were used to develop a multiplex PCR assay. A total of 143 UPEC isolates representing 99 different MLST clones from three locations (North West and South West England and Riyadh, Saudi Arabia) were used to validate the PCR assay. Results. : The multiplex PCR readily identified all 29 E. coli ST127 isolates but, equally importantly, produced no false positives with representatives of any of the other 98 STs tested. Conclusion. : We report the design and validation of a specific multiplex PCR for the rapid and reliable identification of ST127, which can be used for enhanced surveillance for this high‐risk clone.